Tailored Endoscopic Approaches for Pancreatic Traumatic Injuries - Lorenzo Dioscoridi (Pancreas, 2024)
Pancreatic traumatic injuries should be managed by multidisciplinary approach. Standard redo surgery can be avoided or supported by innovative mininvasive approaches both endoscopically and/or radiologically. Pancreatic endotherapy has an increasing role in the management of pancreatic injuries. Understanding the pathophysiology of pancreatic leak is crucial to guide the treatment. Endoscopic treatment must be tailored on the type and site of pancreatic fistula to achieve the optimal clinical outcome: there is not a one-way standard treatment but the best treatment for different types of pancreatic injuries considering both retrograde and endoscopic ultrasound (EUS)-guided approaches.